Achieving the ASEAN Economic Community 2015 - Das, Sanchita Basu (Institute of Southeast Asian Studies, 2012)
Includes index; 1. Introduction: State of Readiness of ASEAN Economies and Businesses, by Sanchita Basu Das -- 2. ASEAN's Readiness in Achieving the AEC 2015: Prospects and Challenges, by S. Pushpanathan -- PART I: CHALLENGES FOR MEMBER COUNTRIES -- 3. Achieving the AEC 2015: Challenges for Brunei Darussalam, by Lim Jock Hoi -- 4. Achieving the AEC2015: Challenges for Cambodia and its Businesses, by Chan Sophal and Larry Strange -- 5. AEC 2015, Cambodia, and the Lao PDR: View from the GMS, by Pradeep Srivastava -- 6. Deadline 2015: Assessing Indonesia's Progress towards the AEC, by Hadi Soesastro and Raymond Atje -- 7. Towards an Integrated AEC: Where is Malaysia? by Rajah Rasiah -- 8. Achieving the AEC 2015: Challenges for the Philippines, by Jenny D. Balboa, Fatima Lourdes E. Del Prado, and Josef T. Yap -- 9. ASEAN Economic Integration: Perspectives from Singapore, by Ong Keng Yong -- 10. Achieving the AEC 2015: Challenges for Thailand, by Nipon Poapongsakorn -- 11. Achieving an Efficient AEC by 2015: A Perspective from Vietnam, by Vo Tri Thanh -- PART II: CHALLENGES FOR THE PRIVATE SECTOR -- 12. ASEAN Economic Integration: Challenges to Brunei Businesses, by Pushpa Thambipillai -- 13. Perspectives of the Indonesian Business Sector on the Regional Integration Process, by Widdi Mugijayani and Pratiwi Kartika -- 14. Achieving the AEC 2015: Challenges for the Malaysian Private Sector, by Mahani Zainal Abidin, Loh Geok Mooi, and Nor Izzatina Abdul Aziz -- 15. Role of the Private Sector in Regional Economic Integration: A View from the Philippines, by Maureen Ane d. Rosellon and Josef T. Yap -- 16. Role of the Singapore Private Sector in ASEAN Economic Integration, by Juliana Giam --17. Thailand's Perspective on the Role of the Private Sector in the Process of Regional Integration, by Eggaluck Suwannakarn and Pisesporn Wasawong -- 18. The Private Sector's articipation in Regional Integration: A Perspective from Vietnam, by Vo Tri Thanh and Nguyen Anh Duong -- PART III: CONCLUSION AND RECOMMENDATIONS -- 19. Conclusion and Recommendations for an Effective AEC, by Sanchita Basu Das -- Index